Leadership in war essential lessons from those who made history - Roberts, Andrew 1963 (Viking, 2019)
"A comparison of nine leaders who led their nations through the greatest wars the world has ever seen and whose unique strengths--and weaknesses--shaped the course of human history, from the bestselling, award-winning author of Churchill and Napoleon Taking us from the French Revolution to the Cold War, Andrew Roberts presents us with a bracingly honest and deeply insightful look at nine major figures in modern history: Napoleon Bonaparte, Winston Churchill, Adolf Hitler, Joseph Stalin, Franklin D. Roosevelt, Charles de Gaulle, Horatio Nelson, Margaret Thatcher, and George Marshall. Each one of these leaders fundamentally shaped the outcome of the war their nation was embroiled in. In what ways were they alike, and in what ways did they differ? Is war leadership unique, or did these leaders have something in common, traits and techniques that transcend time and place and can be applied to the fundamental nature of conflict? Meticulously researched and compellingly written, Leadership in War presents readers with fresh, complex portraits of leaders who approached war with different tactics and different weapons, but with the common goal of success in the face of battle. Both inspiring and cautionary, these portraits offer important lessons on leadership in times of struggle, unease, and discord. With his trademark verve and incisive observation, Roberts reveals the qualities that doom even the most promising leaders to failure, and the qualities that lead a person to victory"--